Early Efforts in Experimental Archaeology: Examples from Evans, Pitt-Rivers, and Abbott - Carolyn Dillian (EXARC Journal)
Experimental archaeology formally began more than 150 years ago with attempts in replicative flint knapping by well-known archaeologists such as Sir John Evans, Augustus (Lane Fox) Pitt-Rivers, John Lubbock, and Sven Nilsson (Coles, 1973). These individuals sought to discover how stone tools were made in order to better identify archaeological artifacts as the products of human manufacture and to understand the process by which they were made. However, the history of experimental archaeology encompasses more than just attempts to replicate stone tools. It needs to be contextualized within debates about the antiquity of humankind and the development of archaeology as professional science.